Identification and validation of expression and functions of ferroptosis-related gene HILPDA in early-onset preeclampsia placentas - Wang, Qianghua; Wang, Xuegu; Fei, Jiaojiao; Jiang, Chuanyue; Tao, Yafen; Yang, Nana; Chen, Huijuan; Dou, Chengli; Ding, Biao; Du, Danli; Li, Xiang (Frontiers in Immunology, 2025)
BackgroundEarly-onset preeclampsia (EOPE) is a severe form of preeclampsia that mainly contributes to maternal and perinatal morbidity and mortality worldwide. This study aimed to systematically analyze the expression and function of ferroptosis-related gene HILPDA in EOPE placentas.MethodsWe included five transcriptomic datasets (GSE148241, GSE44711, GSE74341, GSE114691, GSE10588) downloaded from the Gene Expression Omnibus (GEO) in this study. Using differential expression analysis, weighted gene co-expression network analysis (WGCNA), and machine learning models (LASSO, SVM-RFE, Random Forest), We identified hub genes and diagnostic biomarkers. We performed functional enrichment (GO and KEGG) and immune infiltration analysis to elucidate molecular mechanisms. Experimental validation included Western blot on clinical placental samples and siRNA-mediated knockdown in HTR-8/SVneo trophoblasts to assess migration.ResultsWe observed HILPDA upregulation and confirmed its diagnostic accuracy (AUC=0.71) in EOPE placentas. Functional analysis revealed HILPDA-associated enrichment in immune regulation (leukocyte migration, MHC complexes) and cellular processes (collagen organization, HIF-1 signaling). Through WGCNA, we identified 171 HILPDA-associated DEGs. Machine learning prioritized PART1 as diagnostic biomarkers. Immune profiling highlighted HILPDA’s correlation with activated dendritic cells, neutrophils and resting mast cells. Experimentally, we confirmed HILPDA up-regulation in EOPE placentas and its critical role in suppressing trophoblast migration.ConclusionsOur study establishes HILPDA as a central mechanistic regulator involved in placental immune dysregulation and trophoblast migration in EOPE pathogenesis. The identified biomarkers PART1 and HILPDA-associated pathways may offer novel diagnostic and therapeutic targets for EOPE management, which contribute to reduce maternal morbidity and prevent perinatal mortality in this catastrophic pregnancy syndrome.